A novel view on the pathogenesis of complications after intravesical BCG for bladder cancer. (July 2018) - Bilsen, Manu P.; van Meijgaarden, Krista E.; de Jong, Hanna K.; Joosten, Simone A.; Prins, Corine; Kroft, Lucia J.M.; Jonker, Jacqueline T.; Crobach, Stijn; Pelger, Rob C.; Ottenhoff, Tom H.M.; Arend, Sandra M.
Highlights: Four cases are used to illustrate the spectrum of serious complications after intravesical bacillus Calmette-Guérin (BCG). Infection and inflammation may both play a role in the pathogenesis. Antibiotic therapy is required for local or systemic BCG infection. Systemic signs of inflammation may require the addition of prednisone. A novel BCG killing assay holds promise for understanding the pathogenesis. Abstract: Intravesical bacillus Calmette-Guérin (BCG) is widely used for high-risk, non-muscle-invasive bladder cancer. This report describes four cases that illustrate the spectrum of BCG-induced complications, varying from granulomatous prostatitis to sepsis. There is considerable debate regarding whether inflammation or infection is the predominant mechanism in the pathogenesis of BCG disease. In two patients with a systemic illness, the symptoms first resolved after adding prednisone, indicating a principal role for inflammation in systemic disease. In vitro testing of T-cell responses and a mycobacterial growth inhibition assay were performed for these patients with systemic disease. The patient with mild symptoms showed more effective in vitro growth reduction of BCG, while the patient with sepsis and organ involvement had high T-cell responses but ineffective killing. While these findings are preliminary, it is believed that immunological assays, as described in this report, may provide a better insight into the pathogenesis of BCG disease in individual patients, justifying further research.